An Illustrative Review Cryptographic Algorithms for Scada Application in Networking Ntru for Security - Nitin Sudhakar Patil, Shailaja Sanjay Mohite, Ravindra Sadashivrao Apare, Rajesh Bhatt, Akanksha Kapruwan, Manish Saraswat, Akhil Sankhyan, Anurag Shrivastava (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The computational applications and network protection capabilities of mobile and wireless networks have grown exponentially. Cyberattacks and other unlawful activity on commercial and personal networks have increased in recent years. Firewalls and security code fail to secure computer networks. Personal gadget users, company employees, and military personnel realise network defence is crucial. SCADA systems are commonly utilised in Critical Infrastructure Systems to autonomously monitor and control industrial activities. Security concerns are more likely in SCADA design due to its reliance on computers, networks, applications, and programmable controllers. The huge demand for computers among corporations and other organisations has led to the creation of several networks. Computer network attacks have increased in recent years. Cryptographic solutions of these requirements have performance issues in SCADA systems. NTRU, a faster and lighter public key technique for end-to-end security, is used in this research to improve SCADA security requirements.